The Impact of Health Worker Assistance on the Skills of Posyandu Cadres in Measuring the Height of Toddlers - Sumardilah, Dewi Sri; Indriyani, Reni (Poltekkes Kemenkes Tanjung Karang, 2024)
Weight and height measurements are crucial for monitoring toddler growth and enabling early detection of developmental disorders. Cadres at posyandu (integrated health service posts) play an essential role in this monitoring; however, many lack adequate skills. This study employed a pre-experimental design with pre-test and post-test assessments conducted in the Kedondong Health Center area of Pesawaran Regency. The study involved 47 randomly selected active posyandu cadres, focusing on their skills in measuring toddler height. The treatment variable was the support provided by health workers to these cadres. Skill measurements were taken twice: before (pre-test) and after (post-test) assistance. A checklist outlining the steps for measuring children's height was utilized as the assessment tool. Data analysis included the Shapiro-Wilk test for normality and the Wilcoxon test to evaluate differences in skills pre- and post-mentoring. Results demonstrated a significant improvement in average skill scores, with the infant meter increasing from 6.44 to 8.92 and the stadiometer from 6.06 to 9.11. Statistically significant differences were found before and after mentoring for both instruments (p-value=0.012 for the infant meter; p-value=0.000 for the stadiometer). The study recommends that health workers effectively mentor cadres using these measurement tools, aligning with existing standard operating procedures (SOPs).